2017
DOI: 10.3847/1538-4357/aa872a
|View full text |Cite|
|
Sign up to set email alerts
|

Electron Pre-acceleration at Nonrelativistic High-Mach-number Perpendicular Shocks

Abstract: We perform particle-in-cell simulations of perpendicular nonrelativistic collisionless shocks to study electron heating and pre-acceleration for parameters that permit the extrapolation to the conditions at young supernova remnants. Our high-resolution large-scale numerical experiments sample a representative portion of the shock surface and demonstrate that the efficiency of electron injection is strongly modulated with the phase of the shock reformation. For plasmas with low and moderate temperature (plasma … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
114
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(122 citation statements)
references
References 30 publications
(84 reference statements)
8
114
0
Order By: Relevance
“…We show that reconnecting current sheets are present within a disordered transition region close to the shock ramp, which is consistent with the appearance of these structures in recent hybrid and kinetic shock simulations (Bohdan et al, 2017;Gingell et al, 2017;Matsumoto et al, 2015). We show that reconnecting current sheets are present within a disordered transition region close to the shock ramp, which is consistent with the appearance of these structures in recent hybrid and kinetic shock simulations (Bohdan et al, 2017;Gingell et al, 2017;Matsumoto et al, 2015).…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…We show that reconnecting current sheets are present within a disordered transition region close to the shock ramp, which is consistent with the appearance of these structures in recent hybrid and kinetic shock simulations (Bohdan et al, 2017;Gingell et al, 2017;Matsumoto et al, 2015). We show that reconnecting current sheets are present within a disordered transition region close to the shock ramp, which is consistent with the appearance of these structures in recent hybrid and kinetic shock simulations (Bohdan et al, 2017;Gingell et al, 2017;Matsumoto et al, 2015).…”
Section: Introductionsupporting
confidence: 87%
“…Magnetic reconnection, for which localized changes in magnetic topology result in rapid transfer of energy from fields to particles, has been observed in detail by Magnetospheric Multiscale (MMS) at Earth's magnetopause and more recently in the turbulent magnetosheath (Phan et al, 2018). In the standard model, reconnection occurs within an electron-scale diffusion region (Bohdan et al, 2017;Vasyliunas, 1975), while at ion scales coupled ions are ejected from the diffusion region as bidirectional jets (Gosling et al, 2005;Paschmann et al, 1979;Phan et al, 2000). In the standard model, reconnection occurs within an electron-scale diffusion region (Bohdan et al, 2017;Vasyliunas, 1975), while at ion scales coupled ions are ejected from the diffusion region as bidirectional jets (Gosling et al, 2005;Paschmann et al, 1979;Phan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karimabadi et al () demonstrated by both hybrid simulations and fully kinetic simulations that reconnection occurs in turbulence in the Earth's magnetosheath. Matsumoto et al () and Bohdan et al () studied high Alfvén Mach number ( M A ~30 to 40) perpendicular shocks, and reconnection occurs in the transition region due to Weibel instability. Gingell et al () demonstrated by hybrid simulations that in the Earth's quasi‐parallel bow shock, reconnection occurs in both the transition and downstream regions.…”
Section: Introductionmentioning
confidence: 99%
“…Only if the large-scale magnetic field is oriented strictly out of the simulation plane, the Larmor orbit of reflected ions, and hence the streaming velocity relative to the incoming electrons, δv, is contained in the simulation plane, and the Buneman waves with k δv are fully captured. Bohdan et al [34] present modified versions of equation 35 and 36 that are supposed to account for the projection effect but do not work perfectly, possibly on account of a modified alignment of the motional electric field and the equipotential surfaces of the Buneman waves in simulations with homogeneous magnetic field in the simulation plane.…”
Section: Quasi-perpendicular Shocksmentioning
confidence: 99%